2022
DOI: 10.3390/v14071576
|View full text |Cite
|
Sign up to set email alerts
|

EpiRegress: A Method to Estimate and Predict the Time-Varying Effective Reproduction Number

Abstract: The time-varying reproduction (Rt) provides a real-time estimate of pathogen transmissibility and may be influenced by exogenous factors such as mobility and mitigation measures which are not directly related to epidemiology parameters and observations. Meanwhile, evaluating the impacts of these factors is vital for policy makers to propose and adjust containment strategies. Here, we developed a Bayesian regression framework, EpiRegress, to provide Rt estimates and assess impacts of diverse factors on virus tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This approach shares similarities with EpiRegress and the method proposed by Flaxman et al. ( Flaxman et al., 2020 ; Jin et al., 2022 ). Periodicity was observed in estimates of in both the simulations and case studies, probably because mobility patterns, an important driver of the linear predictors ( Table 1 ), tended to have a weekly cycle.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This approach shares similarities with EpiRegress and the method proposed by Flaxman et al. ( Flaxman et al., 2020 ; Jin et al., 2022 ). Periodicity was observed in estimates of in both the simulations and case studies, probably because mobility patterns, an important driver of the linear predictors ( Table 1 ), tended to have a weekly cycle.…”
Section: Discussionmentioning
confidence: 95%
“…In previous work, the authors developed EpiRegress to provide real-time estimation ( Jin et al., 2022 ), wherein the time-varying reproduction number is taken to be the product of the effects of a diverse set of exogenous factors, including but not limited to mobility patterns and non-pharmaceutical interventions, and is linked to daily case counts through a negative binomial relationship. EpiRegress showed that the introduction of external data can effectively reduce uncertainty in the estimation of in low-incidence scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The R t of the model was quantified using the EpiNow2 package (https:// cran.r-proje ct. org/ web/ packa ges/ EpiNo w2) [30]. It estimates the time-varying reproduction number of infectors through the date of infection.…”
Section: Covid-19 Outbreak Definitionmentioning
confidence: 99%
“…Ho et al (2023) estimates R t while monitoring the time-varying level of overdispersion. There are other spline-based approaches such as Azmon et al (2014); Gressani et al (2022a), autoregressive models with random effects (Jin et al, 2023) that are robust to low incidence, and generalized autoregressive moving average (GARMA) models (Hettinger et al, 2023) that are robust to measurement errors in incidence data.…”
Section: Introductionmentioning
confidence: 99%